Pengaruh Dana Zakat Terhadap Pembangunan Manusia - Mudita Sri Karuni (I-Finance Journal, 2020)
The problem of poverty in Indonesia is the manifestation of society empowerment in accessing state development outcomes. Meanwhile, the result of development done by the government are only enjoyed by a handful of people because the resource is not equitably distributed. Therefore, the role of zakat is needed to give direct fund to redistribute the weatlh, so that human development can be realized. This research aimed to give the empirical result whether zakat has influence on human development in Indonesia. This research used Human Development Index (HDI) indicator as analysis tool, such as life expectancy, mean year school, and income. Hypotheses testing conducted in 15 years (2004-2018). Data collection is done by the documentation method. From the regression analysis of Ordinary Least Square (OLS), it is found that zakat can increase human access to health care, education, and can raise revenues. This study provided implication for governments, zakat institutions, and Muslim communities who are obligated to pay zakat, in order to synergize the optimization of zakat funds in Indonesia.